Effect of Feeding Distillers Dried Grains with Solubles (DDGS), and Legume Non-Legume Roughage on Growth Rate and Haematological Profile of Crossbred Heifers - Dhami, Arjan J.; Patel, Dhaval N.; Pathan, Mohsinkhan M.; Shah, Shailesh V.; Lunagariya, Pravinchandra M. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was undertaken on HF x K heifers (n=24) to evaluate the effect of feeding distillers dried grains with soluble (DDGS) and Soy DOC alone or in combination with cereal and/or legume straws as TMR from average 8 months till 19 months of age on their growth, health and haematological profile. Heifers were uniformly distributed into six treatment groups and were fed concentrate and roughage 50-50 ratio. They were offered three different types of concentrates containing 0, 20 and 40% rice DDGS, each half with wheat straw (25%) and another half as a mixture of wheat straw and groundnut gotar. Heifers were also offered green hybrid Napier @ 2 kg/h/d up to 100 kg BW and 4 kg/h/d for above 100 kg BW and Amul’s Chelated Mineral Mixture @ 35 g/animal/d. The protein requirement was met as per the ICAR (2013) feeding standard. Heifers were offered measured extra wheat straw if no leftover was observed from next day. Higher body weight gain (BWG) was observed in 40% DDGS and legume straw fed groups as compared to 40% soy DOC and cereal straw fed groups. The average Hb, PCV and MCHC were significantly (p<0.05) higher, while WBCs and Platelets were lower in T2 group heifers fed concentrate with 20% soya DOC + 20% RDDGS, irrespective of roughage, as compared to 40% soya DOC (T1) and 40% RDDGS (T3), and there was no significant effect on RBCs, granulocytes, lymphocytes and monocytes. When concentrate source was ignored, only the platelet count was significantly higher in R2 group fed a mixture of legume-nonlegume than R1 group fed only the wheat straw in TMR. There was significant (p<0.05) interaction between concentrate and roughage source on WBC count. Lowest WBC (103/µL) count was found in T1R1 and highest in T1R2 group crossbred heifers. The effect of period x treatment was significant particularly on WBCs, granulocytes and monocytes for first 3-4 months of feeding, perhaps due to adaptive effect of solvent present in RDDGS. Overall the average haematological profile in experimental heifers was close to the reference range for healthy bovine. So it can be concluded that feeding DDGS in place of soy DOC in concentrate and feeding a mixture of groundnut gotar and wheat straw to growing crossbred heifers from 8 months till puberty/19 months improves growth rate without adverse effect on the health and haematological profile.